Finite Element Modeling of Crack Generation in Laser Shock Peening Processed Airfoils - Fang Li; Xue Qi; Dan Xiang (Advances in Materials Science and Engineering)
Laser shock peening (LSP) is a surface treatment process for airfoils that is achieved by the induction of compressive stress. While LSP is a mature and reliable surface treatment process, slight anomalies during the process, or variations in material ductility and geometries, may cause unintended formation of small subsurface cracks in the resultant LSP processed material. In this study, we developed a 3D FEM model to simulate the formation and predict the sizes of cracks generated by inappropriate LSP processing in airfoil specimens in order to avoid producing such subsurface cracks. The Johnson-Cook plastic material model along with the consideration of effects of high strain rate was used to describe the plasticity of Ti alloys. The constants in this plastic model have been optimized with experimental data. The FEM model also includes both damage initiation and evolution criteria to simulate cracks generated by LSP process in the specimens. The simulated crack sizes and locations in the specimens have been validated by the experimental results.